Interculturality as Paradigm to Promote Social and Environmental Sustainability - Le Duc, Anthony (Problemy Ekorozwoju, 2024)
In today’s rapidly changing multicultural world characterized by numerous challenges ranging from geopolitical tensions and interreligious conflicts to environmental degradation, it is imperative to have a paradigm of cultural interaction that promotes social and environmental sustainability. Interculturality has emerged as a relevant framework for addressing these challenges. This paper explores the potential of interculturality to contribute to a more sustainable future by integrating social and ecological dimensions embedded in the paradigm. Therefore, this paper sets out to address the following: (1) Present the concept of interculturality and its relevance to the contemporary milieu; (2) Discuss the contribution of interculturality to promoting social sustainability; (3) Discuss the relationship between culture and nature; and (4) Discuss the potential of interculturality to contribute to environmental sustainability. This paper contributes to ongoing discourse on interculturality by demonstrating not only its relevance to social sustainability but also its implications for environmental sustainability, including raising awareness about the impact of development on culturally significant natural areas, protecting indigenous communities’ rights, and valuing diverse cultural practices for biodiversity management, ultimately contributing to a more sustainable and inclusive society that values all cultures.